Development of a forehand smash stroke model in table tennis for elementary school students - Muhamad Apriyawan Salilama; Sarjan Mile; Suriyadi Datau (Jambura Arena Sport, 2026)
Introduction: This research is driven by a identified research gap, specifically the low level of understanding and technical mastery among elementary school students regarding the forehand smash in table tennis. The urgency lies in providing a systematic and engaging alternative for Physical Education teachers to improve students' basic skills. This study aims to develop and evaluate the effectiveness of a forehand smash learning model at SD Negeri 07 Talaga Jaya. Methods: Using the Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), data were collected through observations, interviews, and validation questionnaires from material and pedagogical experts. Results: The findings revealed that the developed model, featuring a visual instructional guidebook, was declared "Highly Feasible" with an average expert validation score of 4. Small and large-scale trials showed significant improvements in students' cognitive and psychomotor outcomes. Discussion: The novelty of this research is the integration of visual-based learning modified specifically for the physical and psychological characteristics of elementary students. The researcher is confident that the broad implementation of this model will significantly enhance teacher creativity and students' technical skills in table tennis.